(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: The Enhanced Recovery After Surgery (ERAS) guidelines refer to evidence-based perioperative care models aimed at alleviating stress during surgery, reducing complications, and shortening the time needed to recover after surgery. Although they are extensively used in high-income nations, information about their effectiveness in the tertiary care hospitals in Pakistan is scarce. Objective: To determine how effective ERAS guidelines are in preventing postoperative complications, short hospital stay, and recovery outcomes in patients undergoing elective major surgery at Hayatabad Medical Complex, Peshawar. Methods: The study was a randomized clinical trial, which was carried out at Hayatabad Medical Complex, Peshawar between April, 2025 and September, 2025. There were 120 participants in the study whose elective major surgeries were randomly divided into the ERAS group (n=60) and the conventional perioperative care group (n=60). Patients aged 18-65 years with ASA physical status I-II were the inclusion criteria. The exclusion criteria were emergency surgeries, severe systemic illness, and prior major abdominal surgery. ERAS interventions involved preoperative counseling, carbohydrate loading, multimodal analgesia, goal-directed fluid therapy, early oral feeding, and early mobilization. The outcomes after the surgery, such as complications, length of stay, early oral feeding, mobilisation, and opioid intake, were observed and compared with the help of SPSS. Results: ERAS group exhibited much fewer postoperative complications, such as surgical site infections (8.3% vs. 20%), postoperative ileus (6.7% vs. 18.3%), and pulmonary complications (5% vs. 15%) than the conventional care group. Oral feeding and mobilization were much more frequent in the ERAS group (86.7% and 81.7%, respectively), and opioid use decreased (25% vs. 61.7%). The duration of stay in the hospital was also less in the ERAS group (4.2 ± 1.1 days) than in the conventional group (6.8 ± 1.6 days, p = 0.001). Conclusion: ERAS protocols are very effective in minimizing postoperative complications, improving early recovery, and reducing hospitalization. It is suggested that ERAS pathways be adopted in tertiary care hospitals to enhance patient satisfaction and surgical outcomes.